2018
DOI: 10.1212/wnl.0000000000004749
|View full text |Cite
|
Sign up to set email alerts
|

Increased midlife triglycerides predict brain β-amyloid and tau pathology 20 years later

Abstract: ObjectiveTo evaluate the effect of midlife lipid levels on Alzheimer brain pathology 20 years later in cognitively normal elderly individuals.MethodsThis is a longitudinal cohort study of 318 cognitively normal individuals with data on fasting lipid levels at midlife (mean age 54 years). Presence of β-amyloid (Aβ) and tau pathologies 20 years later (mean age 73 years) were detected by quantifying Alzheimer disease (AD) biomarkers in CSF. In a subset (n = 134), Aβ (18F-flutemetamol) PET was also performed.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
68
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 40 publications
(77 reference statements)
1
68
4
Order By: Relevance
“…Our findings appear at odds with one study that reported that these variables did not influence cognition over a 7-year period among non-demented adults living in their 70s (Reitz, Luchsinger, Tang, Manly, & Mayeux, 2005); however, a more recent study found that high triglycerides in midlife were associated with increased risk of AD markers, that is, protein concentrations in cerebrospinal fluid, and evidence of amyloid in tissue during 20 year follow-up imaging (Nägga et al, 2018). Our findings appear at odds with one study that reported that these variables did not influence cognition over a 7-year period among non-demented adults living in their 70s (Reitz, Luchsinger, Tang, Manly, & Mayeux, 2005); however, a more recent study found that high triglycerides in midlife were associated with increased risk of AD markers, that is, protein concentrations in cerebrospinal fluid, and evidence of amyloid in tissue during 20 year follow-up imaging (Nägga et al, 2018).…”
Section: Sensitivity Analysescontrasting
confidence: 99%
“…Our findings appear at odds with one study that reported that these variables did not influence cognition over a 7-year period among non-demented adults living in their 70s (Reitz, Luchsinger, Tang, Manly, & Mayeux, 2005); however, a more recent study found that high triglycerides in midlife were associated with increased risk of AD markers, that is, protein concentrations in cerebrospinal fluid, and evidence of amyloid in tissue during 20 year follow-up imaging (Nägga et al, 2018). Our findings appear at odds with one study that reported that these variables did not influence cognition over a 7-year period among non-demented adults living in their 70s (Reitz, Luchsinger, Tang, Manly, & Mayeux, 2005); however, a more recent study found that high triglycerides in midlife were associated with increased risk of AD markers, that is, protein concentrations in cerebrospinal fluid, and evidence of amyloid in tissue during 20 year follow-up imaging (Nägga et al, 2018).…”
Section: Sensitivity Analysescontrasting
confidence: 99%
“…[12][13][14] However, the evidence is mixed as to whether a relationship exists between vascular risk factors and Aβ burden measured concurrently in older adults, 10,12,15 with recent data from our group suggesting no relationship. [12][13][14] However, the evidence is mixed as to whether a relationship exists between vascular risk factors and Aβ burden measured concurrently in older adults, 10,12,15 with recent data from our group suggesting no relationship.…”
mentioning
confidence: 78%
“…[12][13][14] However, the evidence is mixed as to whether a relationship exists between vascular risk factors and Aβ burden measured concurrently in older adults, 10,12,15 with recent data from our group suggesting no relationship. 14,16,17 Additionally, a recent autopsy study identified an association between late life systolic blood pressure and tau pathology burden. 14,16,17 Additionally, a recent autopsy study identified an association between late life systolic blood pressure and tau pathology burden.…”
mentioning
confidence: 78%
“…TG‐induced central leptin resistance was hypothesized to be the cause . Human studies proposed that high TG compromises blood–brain barrier, and demonstrated that high TG is associated with future increased cerebral β‐amyloid/tau pathology . On the other hand, the observed association between TG and PD‐MCI could also be attributed to factors that impact both lipid metabolism and cognition, such as diet, physical activity, and genetics, which warrant further exploration.…”
Section: Serum Tg Level and Its Associations With Pd‐mci As Well As Cmentioning
confidence: 99%